Antihistamines in the treatment of allergic rhinitis in children - A.E. Abaturov; E.L. Krivusha; V.L. Babich (Zaslavsky O.Yu., 2018)
The review of the literature provides current information about the clinical efficacy, safety and tolerability of the classic second-generation H1-antihistamine, desloratadine, in the treatment of allergic rhinitis in children. For writing the article, we used such databases, as Scopus, Web of Science, MedLine, PubMed, Google Scholar. A brief description of the pharmacokinetics and pharmacodynamics of desloratadine, which is a potent and selective inverse agonist for H1-receptors, with the longest half-life, does not penetrate the blood-brain barrier and does not have a sedative effect. Attention is focused on the ability of desloratadine not only to effectively inhibit histamine-associated clinical manifestations of allergic rhinitis, but also to inhibit the activity of the inflammatory process by decreasing the activity of transcription nuclear factor kappa B. Scientific studies demonstrate a high efficacy of desloratadine in the relief of clinical manifestations of allergic rhinitis in children and a good safety profile during its use.